Sketching your favorite subjects in pen and ink - Nice, Claudia, 1948- (Cincinnati, Ohio : North Light Books, 2003)
n Sketching Your Favorite Subjects in Pen and Ink , Claudia Nice covers all aspects of pen and ink drawing. You'll find complete instruction for and demonstration of techniques such as crosshatching, stippling, texture and value contrasts, as well as the use of contour, parallel and scribble lines. All of theses techniques are illustrated throughout by the author's striking works. You'll find chapters detailing: Houses and Buildings : using freehand and architectural styles, learn to detail barns, houses and cityscapes. Animals : draw realistic animals by focusing on anatomy, facial features and hair texture. The Plant Kingdom : learn to sketch plants, flowers, leaves and trees - from an individual flower to an entire forest. Faces and Figures : sketch realistic, dynamic figures and capture varying moods. Birds : learn to draw lifelike feathers, eyes, bills and feet. Waterscapes : capture the reflections of a quiet brook and the spray of crashing surf.
t t t t t t t
Includes index.
Keywords: Pen drawing -- Technique